Updating Unsignalized Intersection Performance: A Case Study in Indonesian Cities (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper focuses on updating the performance of unsignalized intersections based on the 1997 Indonesian Highway Capacity Manual (IHCM). More than two decades since its publication, IHCM has never been updated although changes in traffic characteristics have occurred resulted from the increased number of vehicles every year. The research took place in twenty intersections in eight cities in Indonesia representing small, medium, and large cities. Updating was carried out in two stages, the first was updating the value of PCE and the second was updating the value of basic capacity and capacity adjustment factors for unsignalized intersections. The results of the first stage indicated that there were changes in the value of PCE for all types of vehicles and the results of the second stage indicated an update for the adjustment factors of approach width, left turn, right turn, and minor road flow ratio. Meanwhile, basic capacity factor; median; environmental type, side friction, and non-motorized vehicles; and delay still used equations contained in IHCM. The final results indicated that there was no significant difference between the calculated delay of the updating and the field delay so that the results of the intersection updating in the form of a new formula could be used to accurately measure the performance of unsignalized intersections for current and future traffic. The implication of this research is that this is the first attempt suggesting or considering a new formula for adjusting IHCM in accordance with the latest traffic conditions.